2010
DOI: 10.3390/cancers2041838
|View full text |Cite
|
Sign up to set email alerts
|

NF-κB in T-cell Acute Lymphoblastic Leukemia: Oncogenic Functions in Leukemic and in Microenvironmental Cells

Abstract: Two main NF-κB signaling pathways, canonical and noncanonical, performing distinct functions in organisms have been characterized. Identification of mutations in genes encoding components of these NF-κB signaling pathways in lymphoid malignancies confirmed their key role in leukemogenesis. T-cell acute lymphoblastic leukemia (T-ALL) is an aggressive malignancy of thymocytes that despite significant therapeutic advances can still be fatal. Although mutations in NF-κB genes have not been reported in T-ALL, NF-κB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 128 publications
(199 reference statements)
0
14
0
Order By: Relevance
“…Furthermore, our group has found that expression of the NF‐κB transcription factor RELB in non‐haematopoietic stromal cells contributes to the development of T‐ALL in a mouse model (dos Santos et al , ). RELB is a critical NF‐κB transcription factor that is activated following engagement of tumour necrosis factor receptor (TNFR) superfamily members, thus hinting that TNFR‐like signalling is implicated in T‐ALL (dos Santos et al , ).…”
mentioning
confidence: 99%
“…Furthermore, our group has found that expression of the NF‐κB transcription factor RELB in non‐haematopoietic stromal cells contributes to the development of T‐ALL in a mouse model (dos Santos et al , ). RELB is a critical NF‐κB transcription factor that is activated following engagement of tumour necrosis factor receptor (TNFR) superfamily members, thus hinting that TNFR‐like signalling is implicated in T‐ALL (dos Santos et al , ).…”
mentioning
confidence: 99%
“…Taken together, these results suggest that Cyr61 has an important role in the resistance of ALL cells to Ara-C. Exogenous Cyr61 decreases Ara-C-induced apoptosis through the NF-κB signaling pathway. Several reports have observed constitutive NF-κB activation in ALL cells (29)(30)(31); this pathway could be activated by Cyr61, resulting in cellular proliferation and chemotherapy resistance in ovarian and breast cancer cells.…”
Section: Level Of Cyr61 Expression In All Cell Lines and All Bone Marmentioning
confidence: 96%
“…Pathways related to the downregulated miRNAs were primarily related to TGF‐beta and NF‐κB signaling pathways and to apoptosis. NF‐κB signaling is a well‐known pathway involved in T‐ALL leukemogenesis due to pathway constitutive activation as well as through its antiapoptotic role . TGF‐beta signaling pathway is an important network involved on the control of hematopoiesis with a suppressing role in the growth of immune cells including T‐cells, and positive effects on T‐cell survival .…”
Section: Discussionmentioning
confidence: 99%